Teaching to Read Multimodal Texts at Tertiary Education: Learning about Gender and Culture with Oxfam Intermón’s Covers - María Martínez Lirola (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2019)
Using multimodal texts in a language classroom offers many opportunities for the development of multiliteracies and the acquisition of different types of competences. The study, thus, aims to deepen into the different social competences university students can acquire when multimodal texts from Non-Governmental Organizations (NGOs) are used in a language classroom. The texts selected are useful to introduce gender issues in the classroom. The methodology is qualitative. For its framework of analysis, the study draws on the main principles of visual grammar (Kress and van Leeuwen, 2006) so that students learn how to analyse visuals. It was decided to use texts from the NGO Oxfam Intermón in which women from other cultures appeared because they allow students at tertiary level develop critical thinking and respect for cultural diversity, which will contribute to the development of social competences. The study reveals that multimodal texts from NGOs are useful to develop critical thinking, to bring cultural aspects into the classroom and to work on social competences.